Relationship of nutritional status with school performance in primary students - Jaramillo-Falcón, Ennis S. (2019)
This research was done to establish the relationship between the nutritional status and school performance in primary students of 32009 from San Sebastián de Quera, district of Santa María del Valle – 2012. The methodology used was correlational design and to demonstrate the hypothesis the analytical method was used. Results: according to nutritional status we have a higher percentage with chronic malnutrition 60.7%, normal students 37.1 % and thin students 2.2%; in terms of school performance we have: very good performance 2.2%, good 65.2%, regular 27.0% and bad 5.6% and in the bivariate analysis between School Performance (DV) and the nutritional status (IV), there is no statistically significant relationship (P=0.327), since a statistically association corresponds to P<0.05. When establishing the correlation between nutritional status and school performance for qualitative variables, the statistical Tau b of Kendall was 0.024, which found no statistically significant relationship (=0.810), since this value is greater than 0.05, so it does not show association. Conclusions: the nutritional status in students was mostly inadequate (62.9%) with chronic malnutrition and thinness, related to carbohydrate-base food; the school performance in students was good and very good (67.4 %), no statistically significant relationship between nutritional status and school performance.